First Sequencing of Caprine Mdr1 (Abcb1) mRNA Due to Suspected Neurological Adverse Drug Reaction in a Thuringian Goat Following Extra-Label Use of Doramectin - Nürnberger, Daniela; Müller, Simon F.; Hamann, Melanie; Geyer, Joachim (Frontiers in Veterinary Science, 2021)
The multidrug resistance gene MDR1 encodes for an efflux transporter called P-glycoprotein (P-gp). In the canine Mdr1 gene, a nonsense mutation was identified in certain dog breeds causing increased drug sensitivity to various P-gp substrates such as antiparasitic macrocyclic lactones. Symptoms of neurologic toxicity include ataxia, depression, salivation, tremor, apparent blindness and mydriasis. In the current report, a Thuringian goat developed similar neurological signs after treatment with doramectin, a compound from the macrocyclic lactone class. Therefore, Mdr1 might be defective in this individual goat. For diagnostic purpose, sequencing of the complete mRNA transcript coding for caprine Mdr1 was performed to investigate a potential missense mutation. The Mdr1 transcripts of two related goats without drug sensitivity were also sequenced to allow differential diagnosis and were compared to the suspected drug sensitive goat. The only position where the Mdr1 sequence from the suspected drug sensitive goat differed was in the 3’-untranslated region, being a heterozygous single nucleotide polymorphism c.3875C>A. It can be suspected that this variant affects the expression level, stability or translation efficiency of the Mdr1 mRNA transcript and therefore might be associated with the suspected drug sensitivity. To clarify this, further studies are needed, particularly investigating the Mdr1 mRNA and protein expression levels from brain material of affected goats. In conclusion: Mdr1 variants may not only exist in dogs, but also in individual goats. The current report provides the first Mdr1 mRNA transcript sequence of a goat and therefore represents the basis for more detailed Mdr1 sequence and expression analyses.